Ius Constituentum Election Courts in Indonesia Ahead of National Simultaneous Elections - Taufik Firmanto; Sukirman Sukirman (Lembaga Penelitian dan Pengabdian Masyarakat, 2022)
Prior to the Implementation of National Simultaneous Elections in Indonesia, Ius Constituents of the Election Court. The purpose of this research is to examine the Election Court's Ius Constituendum in Indonesia, precisely how this Special Court is based on the PTUN environment and is placed in each province capital. This study employs normative juridical research, which is concerned with applying rules or norms in positive law. With a legal perspective (statute perspective), a conceptual perspective (conceptual perspective), and a case perspective (case approach). The results of this study show that the institution of a special election court/election in line with the democratic rule of law principles is necessary, as indicated by the following options: Establishment of a special election court/election inside the Administrative Court, to be known as the Election Court. The Administrative Court houses this Special Court, which is located in each province's capital. This Court has the jurisdiction to hear and determine Election Results Disputes, Election/Pilkada Crimes, and analyze and adjudicate Election Administration/Election Disputes. The Administrative Court houses this Special Court, which is located in each province's capital. This Court has the jurisdiction to hear and determine Election Results Disputes, Election/Pilkada Crimes, as well as to analyze and adjudicate Election Administration/Election Disputes. The Administrative Court houses this Special Court, which is located in each province's capital. This Court has the jurisdiction to hear and determine Election Results Disputes, Election/Pilkada Crimes, as well as to analyze and adjudicate Election Administration/Election Disputes.